2016
DOI: 10.2527/jas.2015-9376
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of isoquinoline alkaloid supplementation levels on ruminal fermentation, characteristics of digestion, and microbial protein synthesis in steers fed a high-energy diet

Abstract: Four Holstein steers with ruminal and duodenal cannulas were used in a 4 × 4 Latin square design to examine the effect of daily intake of 0, 2, 4 or 6 g/steer of standardized plant extract containing a mixture of quaternary benzophenanthridine alkaloids and protopine alkaloids (QBA+PA) on the characteristics of ruminal fermentation and characteristics of digestion. The basal diet consisted of a steam-flaked corn-based finishing diet that contained 62% corn and 12% sudangrass hay and the rest of diet was compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 39 publications
4
24
0
3
Order By: Relevance
“…Sangrovit® has been demonstrated to elevate daily body weight gain and feed conversion ratio in chickens [12] [13] and optimize the nitrogen utilization and feed digestion in bovine [5] [14]. In swine, Sangrovit® has been evaluated for its effects on stress response and pathogen shedding in finishing pigs [15] and ef-fects on the growth parameters in weaning piglets [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sangrovit® has been demonstrated to elevate daily body weight gain and feed conversion ratio in chickens [12] [13] and optimize the nitrogen utilization and feed digestion in bovine [5] [14]. In swine, Sangrovit® has been evaluated for its effects on stress response and pathogen shedding in finishing pigs [15] and ef-fects on the growth parameters in weaning piglets [3].…”
Section: Introductionmentioning
confidence: 99%
“…Sanguinarine and chelerythrine are bitter in taste and products containing these substances have been used as natural appetizing agents to feed farm animals, such as swine [3], bovines [5], poultry [6] and fish [7]. Swine (Sus scrofa domesticus L.) is one of the most important commercial livestock species that provides more than one third of the meat production in the world [8].…”
Section: Introductionmentioning
confidence: 99%
“…M. cordata extract (MCE)-containing products, with a bitter flavor, have been used as a naturally-derived appetizing agent for addition to the feed of production animals including bovine [6] [7], poultry [8] [9], fish [10] and swine [2] [11] Sangrovit® is a standardized preparation of the botanically-derived feed additive that contains 3.5% MCE (providing at least 1.5% sanguinarine). Dietary supplementation with Sangrovit® has been demonstrated to increase the feed intake and optimize nutrient absorption in chickens and other species [12].…”
mentioning
confidence: 99%
“…The obtained results are in alignment with those obtained by Holtshausen et al (2009), who observed a lower fermentation rate of the diet in the rumen with the reduction of CH 4 production when using plant extracts containing secondary metabolites (saponins). Aguilar-Hernández et al (2016) fed heifers a diet supplemented with Macleaya cordata R.Br. as a source of alkaloids and concluded that there was an improvement in the use of nitrogen compounds in the diet due to the activity of the alkaloids on the amino acid-fermenting bacteria.…”
Section: Resultsmentioning
confidence: 99%